2010
DOI: 10.47102/annals-acadmedsg.v39n8p625
|View full text |Cite
|
Sign up to set email alerts
|

A Clinicopathologic Study of Uterine Smooth Muscle Tumours of Uncertain Malignant Potential (STUMP)

Abstract: Introduction: The clinical management of Smooth Muscle Tumours of Uncertain Malignant Potential (STUMPs) remains controversial because little is known about the natural history of these tumours and pathological classifications do not correlate well with clinical outcomes and therefore cannot direct management. The objective of this study was to review a single institution’s experience with STUMP and recommend a rational clinical approach to the management of patients with this histological diagnosis. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(10 citation statements)
references
References 12 publications
(9 reference statements)
2
7
0
Order By: Relevance
“…As shown in Table 2, the median age of women diagnosed with NUBU after surgery was 45 years (IQR 38–49 years), and the incidence of NUBU peaked at 36–45 years and decreased thereafter (Table 2). The median age of NUBU in the present study is comparable to that (41–48 years) of previous studies on NUBU 12–15 . Also, in the previous studies by authors on unsuspected uterine malignancy (UUM) diagnosed after surgery for presumed leiomyoma in the same population, the incidences of UUM diagnosed after hysterectomy, myomectomy, or hysteroscopic myomectomy were 0.19%, 0.12%, and 0.86%, respectively 7–9 .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…As shown in Table 2, the median age of women diagnosed with NUBU after surgery was 45 years (IQR 38–49 years), and the incidence of NUBU peaked at 36–45 years and decreased thereafter (Table 2). The median age of NUBU in the present study is comparable to that (41–48 years) of previous studies on NUBU 12–15 . Also, in the previous studies by authors on unsuspected uterine malignancy (UUM) diagnosed after surgery for presumed leiomyoma in the same population, the incidences of UUM diagnosed after hysterectomy, myomectomy, or hysteroscopic myomectomy were 0.19%, 0.12%, and 0.86%, respectively 7–9 .…”
Section: Discussionsupporting
confidence: 86%
“…Although there are several reports on NUBU diagnosed after surgery for presumed uterine leiomyoma, to our knowledge the present study is the first to report the incidence of NUBU using a large national health insurance database (24 million women annually). [12][13][14][15] In the present study, the incidence of NUBU diagnosed after surgery for presumed leiomyoma was 1.89%. The incidences were 2.03%, 1.84%, and 1.64% for hysterectomy, myomectomy, and hysteroscopic myomectomy, respectively.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Only one of 16 patients experienced recurrence of STUMP (6.3%), giving a lower recurrence rate compared with previous reports for STUMP (7.3%-26.7%) and stage I uterine LMS (72.3%). 5,[7][8][9][10][11] The detailed slide review performed during case selection ruled out three patients with sarcomas that were originally reported as STUMP, which might have reduced the recurrence rate. 5,12 Derman et al 13 reported that six of 21 patients with a final diagnosis of STUMP were initially evaluated with equivocal smooth muscle tumors or LMS before pathologic review.…”
Section: Discussionmentioning
confidence: 99%